Analysis of Bacteria–Phytoplankton relationships at three discrete locations in the Eastern Arabian Sea during winter. (1st July 2022) - Fernandes, Veronica; Bogati, Kalisa
Abstract: Bacterial abundance (BA), bacterial production (BP), chlorophyll a (Chl a ) and primary production (PP) were estimated during Dec 2016–Jan 2017 at three discrete locations viz. the coastal waters, oceanic waters and near coral islands in the eastern Arabian Sea (EAS). During the study period, total bacterial counts were 0.2–1.2 × 10 9  cells L −1 and Chl a concentration was <0.1–1.2 mg m −3 in the EAS. Bacterial carbon (BC) was 50% of the Chl a -carbon representing phytoplankton biomass in all three locations. The BP (0.2–7.2 mg C m −3 d −1 ) was also high relative to the concomitantly measured PP (0.01–17 mg C m −3 d −1 ). Higher ratios of BC:Chl a -C and BP:PP compared to typical ratios in marine environments suggest dominance of allochthonous organic matter. Our analysis indicate that the dissolved organic carbon (DOC) pool which could result from the slow decomposition of the phytoplankton bloom of the preceding southwest monsoon (SWM) season, from the organic matter transported via estuaries and from anthropogenic activities comprises of labile as well as semi-labile components. It possibly fuels much of the bacterial carbon demand that greatly exceeds primary production in all three locations causing net heterotrophic condition which could contribute to increased flux of CO2 to the atmosphere, deoxygenation of coastal waters and threaten fisheries in the EAS during winter. Graphical abstract: Image 1 Highlights: BC biomass comprised 50% of the phytoplankton biomass. BP:PP ratios were 0.5->1. Higher BC:Chl a -C and BP:PP in coastal, coral reef lagoons as well as in open ocean. BC was higher than PP so EAS is net heterotrophic due to allochthonous inputs.